How Elastic is the Demand for Labor? - Clark, Kim B.; Freeman, Richard B. (The Review of Economics and Statistics, 1980)
This paper investigates the magnitude of the elasticity of demand for labor in time series data using more general and complete models of demand than have been previously employed. It argues that previous analyses have imposed two invalid constraints in calculations, which bias downward estimated elasticities. The first invalid constraint is the assumption that real capital prices have an equal opposite effect to real wages in the demand equation. We show on measurement error grounds that this constraint should not be imposed in econometric work even when longrun homogeneity of prices correctly characterizes the market. The constraint is rejected in the data. The second invalid constraint is that all explanatory variables have the same lag distribution. We argue that this constraint is invalid when decisions are made under uncertainty and find that it is also rejected by the data. The principal positive empirical finding is that with the constraints relaxed, the elasticity, of demand with respect to real wages is much larger than the estimates in the literature, indicating much greater price responsiveness on the demand side of the labor market than has previously been thought.